The Effect of Liquidity and Solvency Ratios on the Financial Performance of PT Bank Syariah Indonesia, 2023-2025 - Puteri Anggi Lubis; Yulia Laila (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Financial performance of Islamic banking serves as a crucial indicator in assessing the health and sustainability of financial institutions operating under Islamic principles. This study aims to analyze the effect of liquidity ratio and solvency ratio on the financial performance of PT Bank Syariah Indonesia (BSI) during the 2023 - 2025 period. A descriptive quantitative approach was employed using secondary data derived from BSI's quarterly financial statements published through the Financial Services Authority (Otoritas Jasa Keuangan/OJK). The sample consisted of 12 observation periods, selected using a saturated sampling technique. Data were analyzed using multiple linear regression, accompanied by classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity). The results indicate that, partially, the liquidity ratio had no significant effect on financial performance (sig. = 0.369 > 0.05), whereas the solvency ratio had a significant effect (sig. = 0.025 < 0.05). Simultaneously, both ratios significantly influenced BSI's financial performance (sig. = 0.044 < 0.05), with an R² value of 50.1%. These findings imply that long-term capital management plays a more dominant role in determining BSI's financial performance compared to short-term liquidity management.